2018
DOI: 10.1590/0034-7167-2016-0533
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ knowledge and competencies for preceptorship in the basic health unit

Abstract: it is necessary to discuss and rethink the strategies of interest of preceptors and develop their competencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
26

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 5 publications
0
31
0
26
Order By: Relevance
“…Seventeen competencies with associated methods of assessment were identified, as outlined in Table 2. The methods used to identify competencies of preceptors included expert opinion based on literature reviews and qualitative synthesis (8,9,11,60,61) , Delphi approaches (10,29,32) , and qualitative studies examining the qualities of preceptors that preceptees value most (27,37,42,44,45,51) . Fifteen studies identified competencies, but assessment had not been implemented or reported (8-11, 27, 29, 32, 37, 38, 41, 45, 48, 56, 58, 60) , with only four studies detailing performance indicators for the competencies described (8)(9)(10)(11) .…”
Section: Competencies and Methods Of Assessment Of Preceptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen competencies with associated methods of assessment were identified, as outlined in Table 2. The methods used to identify competencies of preceptors included expert opinion based on literature reviews and qualitative synthesis (8,9,11,60,61) , Delphi approaches (10,29,32) , and qualitative studies examining the qualities of preceptors that preceptees value most (27,37,42,44,45,51) . Fifteen studies identified competencies, but assessment had not been implemented or reported (8-11, 27, 29, 32, 37, 38, 41, 45, 48, 56, 58, 60) , with only four studies detailing performance indicators for the competencies described (8)(9)(10)(11) .…”
Section: Competencies and Methods Of Assessment Of Preceptorsmentioning
confidence: 99%
“…Of the 41 included articles, 26 were conducted in the United States (9, 10, 25, 26, 28-31, 33-36, 38-40, 44-48, 50-52, 56, 59) , three in Canada (8,11,54) , two in Taiwan (42,43) , two in Iran (27) , and one each in Thailand (57) , Ethiopia (53) ,Saudi (24) , Brazil (37) , Australia (49) , Sweden (58) , Belgium (55) and the United Kingdom (32) . Seventeen were based on preceptorship/education in medicine (10, 31, 32, 35, 44, 46, 50-52, 54-56, 58-60) , twelve in pharmacy (9, 11, 24-26, 30, 33, 34, 36, 38, 53, 57) , and eleven in nursing (8,27,28,37,(40)(41)(42)(43)(47)(48)(49) and one in dentistry (45) . There were twelve quantitative studies (25,26,30,33,35,39,46,47,49,53,57) , ten qualitative studies (29,34,37,41,42,44,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 41 included articles, 26 were conducted in the United States (6, 7, 22, 23, 25-28, 30-33, 35-37, 41-45, 7 47-49, 53, 56) , three in Canada (5,8,51) , two in Taiwan (39,40) , two in Iran (24) , and one each in Thailand (54) , Ethiopia (50) ,Saudi (21) , Brazil (34) , Australia (46) , Sweden (55) , Belgium (52) and the United Kingdom (29) . Seventeen were based on preceptorship/education in medicine (7, 28, 29, 32, 41, 43, 47-49, 51-53, 55-57) , twelve in pharmacy (6, 8, 21-23, 27, 30, 31, 33, 35, 50, 54) , and eleven in nursing (5,24,25,34,(37)(38)(39)(40)(44)(45)(46) and one in dentistry (42) . There were twelve quantitative studies (22,23,27,30,32,36,43,44,46,50,54) , ten qualitative studies (26,31,34,38,39,41,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seventeen were based on preceptorship/education in medicine (7, 28, 29, 32, 41, 43, 47-49, 51-53, 55-57) , twelve in pharmacy (6, 8, 21-23, 27, 30, 31, 33, 35, 50, 54) , and eleven in nursing (5,24,25,34,(37)(38)(39)(40)(44)(45)(46) and one in dentistry (42) . There were twelve quantitative studies (22,23,27,30,32,36,43,44,46,50,54) , ten qualitative studies (26,31,34,38,39,41,42,45,55,56) , three mixed methods (40,47,48) , four descriptive papers that did not report results (33,35,37,53) , five papers concerned with validity testing (25,28,49,51,52) and seven papers describing consensus building, three with Delphi approaches…”
Section: Study Characteristicsmentioning
confidence: 99%